Research on the Human Rights and Cultural Protection of Environmentally Displaced Persons under Rising Sea Levels - Rui Xie; Wen-Bo Li; Meng-Chun Lin; Di Lu; Jia-Ming Zhu (Complexity)
In recent years, due to factors such as rising sea levels, several island nations such as Maldives, Tuvalu, Kiribati, and the Marshall Islands are in danger of disappearing completely. When the land of an island country disappeared, the human rights protection of Environmentally Displaced Persons in the migration process and the possible loss of their unique culture, language, and lifestyle have aroused great concern. We call such Environmentally Displaced Persons as EDPs. This study selects the EDPs’ data of 241 countries or regions from 2008 to 2018, establishes an ARIMA model, and predicts the future population of EDPs. By combining the influencing factors of cultural loss, the risk assessment model of cultural loss is established to evaluate the possibility of cultural loss during the migration process of EDPs. We have established a Bayesian Network and a Fault Tree Model to demonstrate the improvement brought about by the implementation of policy recommendations from both qualitative and quantitative perspectives and use the method of fault tree analysis to illustrate the importance of policies from the degree of probability reduction after policy changes. Finally, based on the above model establishment and data analysis, corresponding countermeasures are proposed to protect EDPs’ human rights from being violated and their culture will not be lost.